ANALYSIS OF FAMILY BUSINESS DEVELOPMENT MODEL BASED ON BUSINESS MODEL CANVAS (CASE STUDY IN CV. MXY) - Hermawan, Frendy (Dinasti Publisher, 2020)
Generator set (genset) is one of the solution on overcoming the problem of electricity in Indonesia. CV. MXY, which was established in 2009, is a genset spare parts distributor company headquartered in Jakarta. As a company that belongs to the middle-scale family business group, since its foundation CV. MXY has never had a concept of its business model. Amid the turbulent global economic situation, and the consequences of the Covid-19 pandemic. The company feel the need to make internal improvements in the organization. This was done in order to survive in a very competitive market. The purpose of this research is to identify and design a business model of CV. MXY based on the business model canvas and provides recommendation to companies, with due regard to the condition of family management. This research also to provide insight and alternative choices for family business that are trying to develop their business models. The research method used is a descriptive method based on case studies. Research was conducted in Jakarta in 2020 with data collection techniques carried out through interviews, field observations and library research. From the result of the research can be designed a business model CV. MXY based on business model canvas. In addition, the business model canvas is a simple and easy-to-understand solution as a first step in creating a business model.